Age estimates for female eastern and whitebelly spinner dolphins (Stenella longirostris) incidentally killed in the eastern tropical Pacific tuna purse-seine fishery from 1973-82 - Chivers , Susan J.; Larese , Jason P. (J. Cetacean Res. Manage., 2023)
Age was estimated from teeth for 1,267 female eastern spinner dolphins (Stenella longirostris orientalis) and 1,071 female whitebelly spinner dolphins (S. longirostris) incidentally killed in the eastern tropical Pacific yellowfin tuna purse-seine fishery between 1973 and 1982. The final age assigned to each specimen was the mean of two readers’ age estimates made independently and without knowledge of the corresponding biological data for each specimen. The oldest eastern spinner dolphin was estimated to be 24.5 years and the oldest whitebelly spinner dolphin was 26 years. Age bias plots revealed nonlinear systematic bias between readers while a measure of overall precision, coefficient of variation (CV), indicated equivalent difficulty in estimating age for each population. The age frequency distributions generated in this study document the age structure of dolphins sampled from the observed incidental kill, which will facilitate further assessments of the impact of the fishery on these dolphins.